2015
DOI: 10.1007/s10620-015-3732-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Microwave Ablation in the Spleen for Treatment of Hypersplenism in Cirrhosis Patients

Abstract: AimThe aim of this study was to estimate the feasibility and therapeutic effectiveness of percutaneous microwave ablation in the treatment of hypersplenism in cirrhosis.MethodsForty-one cirrhosis patients with hypersplenism were treated with ultrasonography-guided percutaneous microwave ablation between February 2007 and August 2011. Peripheral blood cell counts, portal vein diameter, splenic vein diameter, and blood flow of splenic vein were evaluated before and after the operation, and complications of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…In our study, complications like pleural effusion, severe pain occurred more in PSE and the two sessions of microwave than one session. This is in agreement with Jiang et al [18], who found less complication in microwave groups than PSE group and increased complications with the increased ablated areas with microwave ablation. Also, this was in agreement to other studies done by Cai et al [19] and Gonsalves et al [20], who found that tense ascites, bacterial peritonitis, and post-embolization syndrome (fever, pain, vomiting) were the complications after PSE.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, complications like pleural effusion, severe pain occurred more in PSE and the two sessions of microwave than one session. This is in agreement with Jiang et al [18], who found less complication in microwave groups than PSE group and increased complications with the increased ablated areas with microwave ablation. Also, this was in agreement to other studies done by Cai et al [19] and Gonsalves et al [20], who found that tense ascites, bacterial peritonitis, and post-embolization syndrome (fever, pain, vomiting) were the complications after PSE.…”
Section: Discussionsupporting
confidence: 93%
“…The retention theory argues that the portal vein pressure will affect the retention time of blood cells in the spleen. The higher the velocity of splenic artery is, the wider the diameter of splenic vein is and the larger the blood flow of splenic vein is, the lower the platelet count will be ( 16 ). The research results showed that the peak velocity of splenic artery in observation group was significantly lower than that in control group after 1 week of treatment, and the diameter, velocity and flow of splenic vein were significantly lower than those in control group (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese researchers have evaluated MWA as a technique to preserve part of the spleen in the treatment of hypersplenism and splenic tumours. For hypersplenism, the higher the splenic volumes that were ablated (over 40-50%), the more the levels of leukocytes, platelets and peripheral lymphocyte subsets improved [77][78][79]. Jiang et al [79] completed the latest study with the largest patient sample and evaluated the effects of MWA in 38 patients with secondary hypersplenism caused by hepatic cirrhosis.…”
Section: Mwa In the Spleenmentioning
confidence: 99%